2018
DOI: 10.1016/j.ajhg.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Truncating Mutations in WASF1 Cause Intellectual Disability with Seizures

Abstract: Next-generation sequencing has been invaluable in the elucidation of the genetic etiology of many subtypes of intellectual disability in recent years. Here, using exome sequencing and whole-genome sequencing, we identified three de novo truncating mutations in WAS protein family member 1 (WASF1) in five unrelated individuals with moderate to profound intellectual disability with autistic features and seizures. WASF1, also known as WAVE1, is part of the WAVE complex and acts as a mediator between Rac-GTPase and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 44 publications
1
38
0
Order By: Relevance
“…1,3,23,[28][29][30][31][32] Variants in both CYFIP2 and WASF1 lead to a similar but unspecific neurodevelopmental phenotype with ID, seizures, and muscular hypotonia, as well as microcephaly, visual impairments and other features in some patients. 5,33 RAC1, ACTB, and ACTG1 variants have also been shown to result in similar overlapping phenotypes. [34][35][36] Although the exact pathomechanisms are yet to be elucidated, the current evidence from fibroblast studies demonstrates an impairment of WRCdependent actin regulation, suggesting that a disturbed actin regulation signaling cascade explains the neurological phenotype of the patients in disorders linked with this pathway.…”
Section: Each)mentioning
confidence: 97%
“…1,3,23,[28][29][30][31][32] Variants in both CYFIP2 and WASF1 lead to a similar but unspecific neurodevelopmental phenotype with ID, seizures, and muscular hypotonia, as well as microcephaly, visual impairments and other features in some patients. 5,33 RAC1, ACTB, and ACTG1 variants have also been shown to result in similar overlapping phenotypes. [34][35][36] Although the exact pathomechanisms are yet to be elucidated, the current evidence from fibroblast studies demonstrates an impairment of WRCdependent actin regulation, suggesting that a disturbed actin regulation signaling cascade explains the neurological phenotype of the patients in disorders linked with this pathway.…”
Section: Each)mentioning
confidence: 97%
“…Rac1 overactivation through loss of RhoGAPs can cause impaired dendritic development and cognition ( ARHGAP15 ) (Zamboni et al 2018a); X-linked intellectual disability ( OPHN1 ) (Busti et al 2020); and deficits in both axonal and dendritic development ( SRGAP s) (Fossati et al 2016; Perez, Sawmiller, and Tan 2016). Downstream of Rac1 in actin polymerization, mutations in PAK s and WASF1 can cause macrocephaly, seizures, intellectual disability, or ASD (Horn et al 2019; Ito et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This appeared puzzling at first glance. However, WAVE1 mutations causing partial WCA domain truncations, thus behaving as dominant negatives, have also been shown to be causative for ID [21]. All this suggests that a precisely tuned, narrow window of WRC activity in the human brain is required for its proper development and function, with both hyper-activation and downregulation leading to similarly drastic consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies found mutations in the NCKAP1 gene, encoding for Nap1, with unknown functions [19,20]. While loss-of-function mutations have been described for the WASF1 gene [21], encoding the protein WAVE1, another recent study found mutations in the RAC1 gene and suggested these mutations to either generate dominant negative or constitutively active alleles [22]. Other studies found mutations in CYFIP2, again causative for neurodevelopmental disorders, which were accused of causing gain-of-function with respect to WRC activation [23,24], but experimental evidence for this assumption was hitherto missing.…”
Section: Introductionmentioning
confidence: 99%